Frizzled 7 and PIP2 binding by syntenin PDZ2 domain supports Frizzled 7 trafficking and signalling - Antonio Luis Egea-Jimenez; Rodrigo Gallardo; Abel Garcia-Pino; Ylva Ivarsson; Anna Maria Wawrzyniak; Rudra Kashyap; Remy Loris; Joost Schymkowitz; Frederic Rousseau; Pascale Zimmermann (Nature Communications, 2016)
PDZ domain-containing proteins are known to function as intracellular scaffolds. Here, Egea-Jimenez et al. report the structure of the tandem PDZ domains of syntenin in complex with a Frizzled 7 peptide and PIP2, show that the ligands bind to syntenin cooperatively and illustrate the role of the complex for Frizzled 7 function.